Green Infrastructure and Healthy Cities: proposal for a Linear Park for the city of Itapuranga, Goiás (Brazil) - Souza, Josimar dos Reis de; Santos, Andressa Rodrigues; Reis, Laís Naiara Gonçalves dos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The instrument called Parque Linear must be, a priori, understood as an important sustainable measure for the use and occupation of urban green areas, in the environmental, social, economic and cultural spheres. These areas, within the Brazilian jurisdiction, are considered by the environmental legislation as Areas of Permanent Preservation (APP), that is, there are a series of prohibitions of constructions and so on. But they are characterized as residual spaces of the remaining natural landscape (when existing) and are, for the most part, invaded and degraded by the urbanization model adopted until today. Due to these problems, many cities in the world and in Brazil have sought to insert this type of park as a measure to mitigate the degraded state in which water courses in urban areas are found, with the aim of improving the quality of life of the population. Thus, this work aims to discuss and demonstrate the relevance of this theme, based on the proposition of Parque Linear in the urban area of Itapuranga, Goiás (Brazil), in the light of the movement for the construction of Healthy Cities, which aims to improve the quality of urban life. As a methodology, bibliographical research, cartographic production, field visit and dialogue with city residents were carried out. The results showed the possibility of installing a linear park adjacent to the GO-230 highway, which cuts through the urban area of the city (urbanized highway), taking advantage of the green areas already present in the stretch, which surround the Tamborim river. In addition, they provided demonstration of the importance of installing this type of instrument to promote the quality of urban life.